The Pemerataan Informasi Sertifikasi Halal Pelaku Usaha di Kecamatan Rancabali Melalui Program Sertifikat Halal Gratis (Sehati) 2023 - Nazla Aulia Saadah; Neneng Windayani; Putri Asti Aprianti; Widi Nurul Zannah (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Equal distribution of information about Halal Certification is important to ensure the halalness of products consumed by the public. The Free Halal Certification Program (Sehati) 2023 was designed by the government to provide quality assurance for halal products for businesses. However, there are still challenges in disseminating information about this program to the public. This research was conducted using community service methods to find the harmony between the government’s function in distributing information to the public. The community’s needs and challenges were analyzed through the survey to measure the public’s understanding of halal certification. The result shows that equal distribution of information from the government to the public has not been made into a priority program, resulting in many people being unaware of the regulation of halal certification. The Kuliah Kerja Nyata (KKN) Tematik Halal Program at UIN Sunan Gunung Djati Bandung in Rancabali District is considered to be helpful in extending the government’s role as an information provider to the public, which shows that cooperative and enthusiasm was found during certification process with the community especially the business actors. This research provides and overview of the challenges and opportunities in distributing halal certification information and provides recommendations for increasing public understanding of The Free Halal Certification Program (Sehati) 2023.